MODEL PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN MATEMATIKA - Arnidha, Yunni; Noerhasmalina, Noerhasmalina (JURNAL e-DuMath, 2018)
This study aims to determine the difference in the mean learning outcomes of mathematics students through model of problem-based learning with the mean mathematics student learning outcomes through the model jigsaw cooperative, and which is higher than both. The population of this study is all students of class VII Mts Miftahul Ulum Gisting which amounted to 56 students. The Sample of this research is the class VII.2 amounted to 23 students as experimental class and class VII.1 amounted to 23 students as control class. Based on the result of hypothesis testing, there are differences in mean learning outcomes between the empirical class and control class, and the average learning outcome of the experimental class is higher than the control class. Keywords: Problem Based Learning, Learning Outcomes